Superior Antibacterial Activity of Integral Lemon Pectin Extracted via Hydrodynamic Cavitation. Issue 5 (28th May 2020) - Presentato, Alessandro; Scurria, Antonino; Albanese, Lorenzo; Lino, Claudia; Sciortino, Marzia; Pagliaro, Mario; Zabini, Federica; Meneguzzo, Francesco; Alduina, Rosa; Nuzzo, Domenico; Ciriminna, Rosaria
Abstract: Pectin extracted via hydrodynamic cavitation in water only from waste lemon peel and further isolated via freeze drying displays significant antibacterial activity against Staphylococcus aureus, a Gram positive pathogen which easily contaminates food. The antibacterial effect of the new IntegroPectin is largely superior to that of commercial citrus pectin, opening the way to advanced applications of a new bioproduct now obtainable in large amounts and at low cost from citrus juice industry's waste. Abstract : Bacteria vs. lemons ! Pectin extracted via hydrodynamic cavitation in water only from waste lemon peel and further isolated via freeze drying displays significant antibacterial activity against Staphylococcus aureus, a Gram positive pathogen which easily contaminates food.